2017
DOI: 10.1103/physrevb.96.134416
|View full text |Cite
|
Sign up to set email alerts
|

Metalliclike behavior of the exchange coupling in (001) Fe/MgO/Fe junctions

Abstract: Exchange magnetic coupling between Fe electrodes through a thin MgO interlayer in epitaxial junctions has been investigated as a function of temperature, MgO thickness, and interface quality. Depending on the MgO thickness, which has been varied from 1.5 to 4 monolayers, two opposite temperature dependences are clearly disentangled. For a thin MgO spacer, the main component decreases with temperature following a metalliclike behavior. On the contrary, for the thickest MgO layers, the main component increases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…The size of the coupling is similar to that found in other studies but in our case it extends through MgO layers which are significantly thicker [8]. The reasons for this are as yet unknown but it has been shown that the size and sign of the coupling is strongly affected by a number of factors such as strain [17], impurities/vacancies in the MgO [13,14,17], and interface roughness [18]. These factors are highly sensitive to the growth conditions which vary somewhat between experiments.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The size of the coupling is similar to that found in other studies but in our case it extends through MgO layers which are significantly thicker [8]. The reasons for this are as yet unknown but it has been shown that the size and sign of the coupling is strongly affected by a number of factors such as strain [17], impurities/vacancies in the MgO [13,14,17], and interface roughness [18]. These factors are highly sensitive to the growth conditions which vary somewhat between experiments.…”
Section: Resultssupporting
confidence: 72%
“…Although the interaction mechanism is different in a metallic superlattice, similar arguments could apply in the Fe/MgO case. In addition, it is known that the interaction can be either ferromagnetic or antiferromagnetic in the Fe/MgO system, depending on the thickness of the layers, strain, and other factors [17] and recently, a metalliclike oscillatory interaction has even been found in very thin MgO layers [18]. Therefore it is not inconceivable that longer-range interactions could have a different sign to the nearest neighbor interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a possibility that, in our case, the tunneling barrier may be very low, which can lead to a considerable increase in the tunneling depth. Moreover, the charge-neutral gap formed by the vacancies can even enable MgO to behave like a metal 38 , in which case the interlayer RKKY exchange constant demonstrates an oscillating-like behavior similar to that observed by us.…”
Section: Resultssupporting
confidence: 82%
“…It should be mentioned that it bears a certain resemblance to the oscillating-like behavior of the interlayer RKKY exchange constant in the case of a conducting spacer. Since the quasi-conducting behavior of MgO spacers has been reported previously 38 , we have developed a simplified theoretical formalism taking advantage of this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…MgO thin films are of particular interest in this context, since high crystalline quality is obtained when governed by cube-on-cube epitaxy. They are quite successfully used in magnetic tunnel junctions as crystalline barriers which, due to a highly spin-dependent evanescent decay of metallic wave functions, give rise to much higher tunnel performance than amorphous films [22][23][24][25][26][27][28] . On Ag(100), the MgO film grows in the form of islands which progressively cover the surface [29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%